1992
DOI: 10.1096/fasebj.6.14.1426763
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transferrin gene expression

Abstract: Transferrin (Tf) is the iron-transport protein of vertebrate serum. It is essentially synthesized in the liver, but lower amounts are also produced in other organs, such as testis and brain. A number of studies have been done to characterize the transcriptional elements implicated in the regulation of Tf gene expression in different organs. The results of these studies support the hypothesis that the Tf gene makes use of different combinations of nuclear proteins in different subsets of cells to achieve tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 40 publications
5
38
0
Order By: Relevance
“…Transferrin protein was decreased Ͼ5-fold at the early time point. Transferrin is the iron transport protein of vertebrate serum that is primarily, although not exclusively, synthesized in the liver (17 ). Transferrin mRNA concentrations are diminished by aflatoxin B-1 exposure in rats (18 ).…”
Section: Proteomics Resultsmentioning
confidence: 99%
“…Transferrin protein was decreased Ͼ5-fold at the early time point. Transferrin is the iron transport protein of vertebrate serum that is primarily, although not exclusively, synthesized in the liver (17 ). Transferrin mRNA concentrations are diminished by aflatoxin B-1 exposure in rats (18 ).…”
Section: Proteomics Resultsmentioning
confidence: 99%
“…The role of nodule and HCC iron content in Tf and Tf-R expression is not clear. Iron cell content may regulate Tf and Tf-R mRNA transcription, 34,38 although, in the case of Tf-R, iron is principally involved in posttranscriptional regulation of Tf-R gene expression by interaction with ''iron-responsive elements'' of Tf-R mRNA. [34][35][36][37] Total iron content in preneoplastic liver nodules is not significantly different from that in normal liver, and is associated with Tf and Tf-R overexpression, while a 160% increase in HCC is paralleled by Tf-R overexpression and marked decrease in Tf expression.…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding is intriguing because, in the DESIR population, as in the other populations, plasma transferrin was negatively correlated with plasma ferritin (r ϭ Ϫ0.289, P Ͻ 0.001); a high iron load is reflected by high ferritin levels but decreased transferrin levels. Little is known about the regulation of transferrin (12). Plasma transferrin itself may be involved in the pathogenesis of insulin resistance because Vargas et al (13) have shown an antagonist effect of human transferrin on insulin action.…”
mentioning
confidence: 99%